Hot pants and spandex suits : gender representation in American superhero comic books - De Dauw, Esther (Rutgers University Press, 2021)
The superheroes from DC and Marvel comics are some of the most iconic characters in popular culture today. But how do these figures idealize certain gender roles, body types, sexualities, and racial identities at the expense of others? Hot Pants and Spandex Suits offers a far-reaching look at how masculinity and femininity have been represented in American superhero comics, from the Golden and Silver Ages to the Modern Age. Scholar Esther De Dauw contrasts the bulletproof and musclebound phallic bodies of classic male heroes like Superman, Captain America, and Iron Man with the figures of female counterparts like Wonder Woman and Supergirl, who are drawn as superhumanly flexible and plastic. It also examines the genre's ambivalent treatment of LGBTQ representation, from the presentation of gay male heroes Wiccan and Hulkling as a model minority couple to the troubling association of Batwoman's lesbianism with monstrosity. Finally, it explores the intersection between gender and race through case studies of heroes like Luke Cage, Storm, and Ms. Marvel. Hot Pants and Spandex Suits is a fascinating and thought-provoking consideration of what superhero comics teach us about identity, embodiment, and sexuality.
Keywords: Comic books, strips, etc. -- United States -- History and criticism.; Superheroes in comics.; Gender identity in comics.; Race awareness in comics.; National characteristics, American, in comics.; Superheroes in literature.; Gender identity in literature.; Race awareness in literature.; Superhéros dans la littérature.; Identité de genre dans la littérature.; Conscience de race dans la littérature.; LITERARY CRITICISM / General.; Superheroes in comics; National characteristics, American, in comics; Gender identity in comics; Comic books, strips, etc.; United States; Gender Studies, Representation, Superhero, Comic Books, DC, Marvel, Pop Culture, Media, Mass Media, Gender Roles, Sexualities, Race, Identity, Golden Age, Silver Age, Captain America, Iron Man, Classics, LGBTQ, Genre, Superman, Legacy, Masculinity, Heroes, Culture, America.; Electronic books.; Comics criticism; Criticism, interpretation, etc.; Comics criticism.; Critiques de bandes dessinées et de romans graphiques.